Association of habits with clinical symptoms in oral submucous fibrosis patients - a retrospective study - MAHAJAN, SAI SUDHA; HANNAH R; RAMANI, PRATIBHA (The journal of contemporary issues in business and government, 2020)
Abstract: Oral Submucous Fibrosis (OSMF) is a potentially malignant disorder and its early diagnosis is essential to reduce malignant transformation into oral squamous cell carcinoma (OSCC) and thereby reduce morbidity and mortality. This study assessed the chewing habits of the patients visiting Saveetha Dental College and Hospitals with regard to consumption of areca nut and its products, frequency and duration of habits as well as clinical symptoms and signs in OSMF. The aim of this study was to associate the habits with clinicopathological findings in OSMF patients. An institutional based retrospective study was conducted among 64 cases clinically diagnosed with OSMF. A detailed habit history and clinical signs and symptoms were recorded and appropriate statistical analysis was done. The study included 62 OSMF cases of both the gender groups; males (87.5%) and females (12.5%) of age group between 22 to 65 years. In this study, the most common habit was noted to be pan chewing and the commonest clinical symptoms was found to be restricted mouth opening (39%) and associated pain symptoms (28%). A very common clinical site for this lesion was found to be the buccal mucosa bilaterally (79.69%). The habit patterns and clinical features of OSMF are important to facilitate prompt diagnosis and management in order to monitor its clinical severity and progression to OSCC.